1984
DOI: 10.1007/bf00277748
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of the cell size distribution

Abstract: Abstract. A model for the growth of a size-structured cell population reproducing by fission into two identical daughters is formulated and analysed. The model takes the form of a linear first order partial differential equation (balance law) in which one term has a transformed argument. Using semigroup theory and compactness arguments we establish the existence of a stable size distribution under a certain condition on the growth rate of the individuals. An example shows that one cannot dispense with this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
207
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(218 citation statements)
references
References 17 publications
(13 reference statements)
7
207
0
Order By: Relevance
“…Simulations showed that constant and quadratic forms of growth achieved balanced time-invariant growth states using equal and unequal partitioning. Under conditions of linear growth and equal partitioning, however, the population distribution appeared to have a periodic behaviour, a special case originally predicted in theory by Diekmann et al (1984) described as a 'multiplication machine'. In all the remaining cases, unequal division resulted in balanced growth being achieved faster and with broader distribution.…”
Section: Nð0 Tþ ¼ 0 ð6þmentioning
confidence: 81%
“…Simulations showed that constant and quadratic forms of growth achieved balanced time-invariant growth states using equal and unequal partitioning. Under conditions of linear growth and equal partitioning, however, the population distribution appeared to have a periodic behaviour, a special case originally predicted in theory by Diekmann et al (1984) described as a 'multiplication machine'. In all the remaining cases, unequal division resulted in balanced growth being achieved faster and with broader distribution.…”
Section: Nð0 Tþ ¼ 0 ð6þmentioning
confidence: 81%
“…Another immediate consequence of (13) Let P be defined by (8) and denote by A b a the differential operator −(gN ) − μN restricted to the domain…”
Section: Formulation Of the Resultsmentioning
confidence: 99%
“…We note that due to (8) and the domain of definition of P , the function Ff is locally integrable on [a, 1) for any f ∈ L ∞ [a, 1]. The following lemma gathers some properties of the operator F .…”
Section: Proposition 1 the Operator B Has An Eigenvector W Which Satimentioning
confidence: 99%
See 1 more Smart Citation
“…Models that do distinguish between growth in biomass and growth in cell number must include separate mechanisms for describing cell growth and fission. Such size-structured models were first developed by Sinko and Streifer [22,23], Bell [3] and Bell and Anderson [4] and were later modified and investigated extensively by Diekmann et al [7,8] and Metz and Diekmann [17].…”
Section: Introductionmentioning
confidence: 99%